Same-Occupation Spouses: Preferences and Search Costs - Hani Mansour; Terra McKinnish (Institute for the Study of Labor (IZA), 2014)
Married individuals match with spouses who share their occupation more frequently than predicted by chance, suggesting either a preference for same-occupation matches or lower search costs within occupation. To distinguish between these explanations, we use a differences-in-differences strategy that compares the difference in wages between same-occupation husbands and different-occupation husbands across occupations with different percent male workers. Under the preferences mechanism, the difference should be decreasing in percent male. Under the search cost mechanism, the difference should be increasing in percent male. Our results are consistent with the search cost explanation, especially in occupations with greater degree of workplace communication.
Keywords: J12; J24; 330; marital sorting; occupation; sex ratio; search frictions